A Statistical Analysis of Determining the Relationship between Academic and Internship Performance in IT interns - MUHAMMAD HASSAN SHAHNAWAZ; Jawahir Che Mustapha Yusuf; Munaisyah Abdullah (Journal of Computing Technologies and Creative Content, 2025)
As internships continue to play a more crucial role in undergraduate degree programs, acting as a link between academic learning and professional work settings, it becomes vital to comprehend the connection between academic performance and internship outcomes. This study aims to underscore the effectiveness of data analytics in uncovering valuable insights that can illuminate the link between academic performance and internship success. A survey was distributed among 182 final-year students at Universiti Kuala Lumpur, a Malaysian university, all of whom had successfully completed their internships. This survey aimed to collect academic grades, feedback, and reflections from these students about their internship encounters. Pearson’s and Linear Regression Correlation analysis was employed to explore and predict the potential influence of academic performance on internship achievements. The evaluation of performance encompassed three key areas: practical skills, ethics and professionalism, and problem-solving capabilities. The results revealed a slight positive correlation between academic and internship grades in the practical skills and problem-solving domains, while a weak negative correlation was identified concerning ethics and professionalism. As a result, the researchers concluded that there are additional factors at play that impact a student’s internship performance. It is not entirely accurate to assert that a student’s strong academic performance guarantees success during internships.